2022
DOI: 10.3390/ph15111432
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Prospect of Gastrodin in Osteoporosis, Bone Regeneration, and Osseointegration

Abstract: Gastrodin, a traditional Chinese medicine ingredient, is widely used to treat vascular and neurological diseases. However, recently, an increasing number of studies have shown that gastrodin has anti-osteoporosis effects, and its mechanisms of action include its antioxidant effect, anti-inflammatory effect, and anti-apoptotic effect. In addition, gastrodin has many unique advantages in promoting bone healing in tissue engineering, such as inducing high hydrophilicity in the material surface, its anti-inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 158 publications
0
4
0
Order By: Relevance
“…Actin filaments at the leading edge of the cell forms lamellar and filamentous pseudopods, generating a force to propel cell migration [ 30 ]. While, the excess ROS can damage the function of actin filaments [ 9 , 31 , 32 ]. In this study, we found that the cells extended a large number of pseudopods while gastrodin acted as an antioxidant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actin filaments at the leading edge of the cell forms lamellar and filamentous pseudopods, generating a force to propel cell migration [ 30 ]. While, the excess ROS can damage the function of actin filaments [ 9 , 31 , 32 ]. In this study, we found that the cells extended a large number of pseudopods while gastrodin acted as an antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…ROS inhibits proliferation and differentiation of osteoblast, and induces autophagy and apoptosis, ultimately leading to a decrease in osteogenesis [ 7 , 8 ]. In addition, ROS inhibits cell migration and adhesion by damaging the function of mitochondria and filaments in the cytoskeleton [ 9 ]. In the face of oxidative stress damage, the defense within the organism mainly includes antioxidant enzymes, supply of their substrates and repair of injury [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori further disrupt the delicate balance by impairing the secretion of bicarbonate, a key component in neutralizing gastric acid. This impairment promotes increased acidity within the gastric environment, creating an ideal milieu for the development and progression of peptic ulcers 34 .…”
Section: Rare Causes Of Pudmentioning
confidence: 99%
“…The study suggested that EPC-EVS could be a preventative measure against glucocorticoid-induced osteoporosis in mice by hindering osteoblasts’ ferroptotic pathway. However, further analysis is necessary to understand ferroptosis mechanisms related to GIOP 75 76 77 .…”
Section: Introductionmentioning
confidence: 99%